26.3k views
5 votes
PLEASE HELP, I NEED TO BE HELPED WITH THESE QUESTIONS

PLEASE HELP, I NEED TO BE HELPED WITH THESE QUESTIONS-example-1
PLEASE HELP, I NEED TO BE HELPED WITH THESE QUESTIONS-example-1
PLEASE HELP, I NEED TO BE HELPED WITH THESE QUESTIONS-example-2
PLEASE HELP, I NEED TO BE HELPED WITH THESE QUESTIONS-example-3
PLEASE HELP, I NEED TO BE HELPED WITH THESE QUESTIONS-example-4

1 Answer

7 votes

Answer:


(f+g)(x)=√(3x+7)+√(3x-7)


f(g(x))=x+1


f(x)=x+9 \text{ and } g(x)=(4)/(x^2)


f^(-1)(x)=\frax{x+2}{3}

Let me know if you have any questions about any of my work.

Explanation:

You are given the following:


f(x)=√(3x+7) \text{ and } g(x)=√(3x-7)

and asked to find
(f+g)(x) \text{ which means } f(x)+g(x).

If you add those because we are asked to find f(x)+g(x) you get:


√(3x+7)+√(3x-7)

----------------------------------------------------------

You are given the following:


f(x)=x^2+3 \text{ and } g(x)=√(x-2)

and asked to find
f(g(x)).


f(g(x))


f(√(x-2)) I replaced g(x) with sqrt(x-2) because that is what it equals.

Now this last thing means to replace old input in x^2+3 with new input sqrt(x-2) giving us:


(√(x-2))^2+3


x-2+3


x+1

------------------------------------------------------------

We are given
y=(4)/(x^2)+9 and asked to find g(x) and f(x) such that y=f(g(x)).

We have choices so let's use the choices:

Choice A:


f(g(x))


f((4)/(x^2)){/tex] &nbsp; &nbsp;I replace g(x) with 4/x^2:</p><p>[tex](4)/(x^2)+9 I replaced the old input x with new input 4/x^2.

This was actually the desired result.

-----------------------------------------------------------

To find the inverse of f(x)=3x-2 or y=3x-2, your objective is to swap x and y and then remake y the subject.

y=3x-2

Swap x and y:

x=3y-2

Now solve for y.

Add 2 on both sides:

x+2=3y

Divide both sides by 3:

(x+2)/3=y

y=(x+2)/3


f^(-1)(x)=\frax{x+2}{3}